Emotional Intelligence and Psychological Perspectives: An Integrative Review for the Contemporary Era - Dr. Pallavi Dubey (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
Emotional Intelligence (EI) has transitioned from a provocative psychological concept to a multidisciplinary field of study with profound implications for understanding the human condition in the 21st century. This paper provides a comprehensive and critical integrative review, dissecting EI through the complementary lenses of psychology and sociology. We begin by meticulously delineating the dominant theoretical models—the ability model, the trait model, and mixed models— and highlighting ongoing psychometric and conceptual debates. The psychological analysis is deepened with a contemporary review of neuroscientific evidence, linking EI to the interplay between the prefrontal cortex, anterior cingulate cortex, and limbic system, and exploring its role as a buffer against psychopathology through the mechanisms of cognitive reappraisal and resilience. From a sociological standpoint, we reframe EI not as an innate trait but as a form of cultural capital, scrutinising its role in social reproduction within educational and corporate institutions in Taiwan. The analysis is extended to the digital realm, examining how Computer-Mediated Communication (CMC) and social media are reshaping the expression and regulation of emotion. Engaging robustly with critical theory, we interrogate the neoliberal co-optation of EI, its potential as a tool for normative control, and the emergence of a "dark side" where emotional skills serve manipulative ends. We conclude that a siloed approach to EI is untenable; its future lies in a holistic, critical, and interdisciplinary paradigm that acknowledges its power at intrapsychic, interpersonal, and institutional levels.
Keywords: emotional intelligence; psychology; sociology; mental health; neuroscience; social capital; digital society; digital emotion; critical theory; neoliberalism; psychopathology